The Impact of Economic Growth and Trade Openness on Environmental Degradation: Evidence from A Panel of ASEAN Countries - A'yun, Indanazulfa Qurrota; Khasanah, Uswatun (Universitas Muhammadiyah Yogyakarta, 2022)
Global warming and climate change show a decrease in environmental quality. The main cause of global warming is the emission of carbon dioxide (CO2). This study aims to analyze the effect of economic growth and economic openness on environmental quality in ASEAN countries from 2010 to 2019. This research uses a panel data analysis method. The analysis results show that the variable economic growth has a negative and significant effect on carbon dioxide emissions. Meanwhile, the variables used for economic openness are exports, imports, and FDI. Export and FDI variables have a positive and significant effect on CO2 emissions, but there is no effect on imports. This study also used population variables as control variables and the result is there is no effect on CO2. Based on the results, it is necessary to have a carbon emission reduction policy for ASEAN countries using environmentally friendly technology.